Artificial Intelligence for Demystifying Blockchain Technology Challenges: A Survey of Recent Advances - Olaniyi, Olayemi Mikail; Alfa, Abraham Ayegba; Umar, Buhari Ugbede (Frontiers in Blockchain, 2022)
Blockchain technology has gained lots of traction in the past five (5) years due to the innovations introduced in the digital currency, Bitcoin. This technology is powered by distributed ledger technology, which is a distributed database system. It is often renowned for decentralization, anti-attack, and unfalsified attributes making it a top choice in several non-monetary applications. The problem of privacy and security of the Internet of Things has been undertaken aggressively with Blockchain. Several problems have been identified with Blockchain technology such as large delays and lack of support for real-time transactions processing, authorization, node verification, and consensus mechanisms. This article intends to provide a comprehensive survey on the recent advances, and solutions to the problems of Blockchain technology by leveraging the Artificial Intelligence approaches. The outcomes of this study will provide valuable information, and guidance on the design of Blockchain-based systems to support time-sensitive and real-time specific applications and processes.